2000
DOI: 10.3171/jns.2000.93.supplement_3.0128
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife thalamotomy for treatment of tremor: long-term results

Abstract: Object. The purpose of this study was to investigate the long-term effects of gamma knife thalamotomy for treatment of disabling tremor. Methods. One hundred fifty-eight patients underwent magnetic resonance imaging—guided radiosurgical nucleus ventralis intermedius (VIM) thalamotomy for the treatment of parkinsonian tremor (102 patients), essential tremor (52 patients), or tremor due to stroke, encephalitis, or cerebral trauma (four patients). Preoperative and postoperative blinded assessments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Although it has been suggested that gamma knife VIM thalamotomy provides tremor relief equivalent to that provided by thalamotomy or deep brain stimulation and may be a safer procedure [77], a recent report by Siderowf et al [78] noted that gamma knife thalamotomy led to a complex, disabling movement disorder in a 59-year-old ET patient who underwent the procedure.…”
Section: Surgical Treatment Of Essential Tremormentioning
confidence: 98%
“…Although it has been suggested that gamma knife VIM thalamotomy provides tremor relief equivalent to that provided by thalamotomy or deep brain stimulation and may be a safer procedure [77], a recent report by Siderowf et al [78] noted that gamma knife thalamotomy led to a complex, disabling movement disorder in a 59-year-old ET patient who underwent the procedure.…”
Section: Surgical Treatment Of Essential Tremormentioning
confidence: 98%
“…Thalamotomy is faster, cheaper, requires only minimal subsequent care, and is generally equally effective, especially for unilateral procedures. • Gamma knife thalamotomy techniques are also being explored but suffer from their inability to record thalamic electrical activity, thus making exact localization difficult [63]. The procedure has the tremendous advantage of being noninvasive, but to date, results have been inconsistent.…”
Section: Thalamotomy and Thalamic Stimulationmentioning
confidence: 99%
“…Microelectrode recordings from a limited number of patients suggest that the T2-hypointense core region represents the directly irradiated zone, while the surrounding irregular T2-hyperintense region is not functionally damaged 77. Tissue reaction can vary, and delayed effects months after the actual treatment have been repeatedly reported, resulting in drastically different lesion sizes between 188 mm 3 and 871 mm 3 97 with exceptional cases as large as 2030 mm 3 after 36 months98 or >6000 mm 3 after 18 months95 (see figure 3). After GK VIM thalamotomy cases without side effects showed smaller lesion sizes of 188±224 mm 3 (n=157 procedures) than cases with side effects: 871±742 mm 3 97.…”
Section: Incisionless Techniquesmentioning
confidence: 99%